Preschool teachers’ STEM pedagogical content knowledge: A comparative study of teachers in Greece and Turkey - Gözüm, Ali İbrahim Can; Papadakis, Stamatios; Kalogiannakis, Michail (Frontiers in Psychology, 2022)
This study compares the STEM Pedagogical Content Knowledge of Greek and Turkish preschool teachers. The present research is a comparative descriptive study that aims to determine the STEM Pedagogical Content Knowledge of preschool teachers from Greece and Turkey. A descriptive survey model, a method used in quantitative research, was used as this study’s primary research method. The STEM Pedagogical Content Knowledge Scale (STEMPCK) was used in this study. Six hundred sixty-nine preschool teachers -- 104 Greek and 565 Turkish teachers -- participated in this study. The STEMPCK Scale’s construct validity and reliability were tested using this study’s data set, which was found to be both valid and reliable. No significant difference was found between the STEMPCK scores of Greek and Turkish preschool teachers. The significant differentiation of STEMPCK scores based on whether the teachers had received any STEM training is discussed in light of the relevant literature. This study determines and compares STEMPCK among preschool teachers from disparate countries such as Greece and Turkey and is expected to contribute to the literature.